2014
DOI: 10.1080/15350770.2014.961826
|View full text |Cite
|
Sign up to set email alerts
|

Lifelong Learning: A Dyadic Ecological Perspective

Abstract: This paper examines lifelong learning in differentiating it from formal education, and emphasizes multiple theoretical perspectives in doing so. The theoretically based approaches emphasized here include contextualism and the multi-layered nature of the environment, the dialectics of interactions among students and instructors, the zone of proximal development, and person-environment fit. Examining lifelong learning from these perspectives deepens our understanding of such learners and has implications for fut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Despite these limitations, the current study contributes to the literature regarding kindergarten teachers' beliefs, the roles of the classroom, and home environments when targeting early math skills as important content knowledge in kindergarten. By conceptualizing children's math experiences using cognitive constructivism (Echevarria & Graves, 2007;Eggen & Kauchak, 2010) and an ecological perspective (Hayslip, 2014;Pelech & Pelech, 2013), based on our findings, we suggest that four elements are important for children's math learning. These elements are reading and singing activities at home, the frequency and duration of math teaching, problem-solving activities in kindergarten classrooms, and arts or life-related materials in kindergarten classrooms.…”
Section: Conclusion/recommendationsmentioning
confidence: 74%
See 1 more Smart Citation
“…Despite these limitations, the current study contributes to the literature regarding kindergarten teachers' beliefs, the roles of the classroom, and home environments when targeting early math skills as important content knowledge in kindergarten. By conceptualizing children's math experiences using cognitive constructivism (Echevarria & Graves, 2007;Eggen & Kauchak, 2010) and an ecological perspective (Hayslip, 2014;Pelech & Pelech, 2013), based on our findings, we suggest that four elements are important for children's math learning. These elements are reading and singing activities at home, the frequency and duration of math teaching, problem-solving activities in kindergarten classrooms, and arts or life-related materials in kindergarten classrooms.…”
Section: Conclusion/recommendationsmentioning
confidence: 74%
“…For children to become effective problem solvers and have proficient math abilities, they require time to consider problems, attempt various strategies, and discuss the problems with their peers, teachers, and other adults (Charlesworth & Lind, 2013;Hou & So, 2017). Ecological perspectives have indicated that an individual's learning occurs in myriad ways and in various contexts (Hayslip, 2014;Leu, 2008;Pelech & Pelech, 2013). Classroom and home learning environments, among others, are critical contexts that need to be carefully considered in combination, as children engage in diverse learning experiences (Cozza & Oreshkina, 2013;Gottfried & Gee, 2017;Hampden-Thompson & Galindo, 2017;Schütte, 2014).…”
Section: Early Experiences and Children's Math Learningmentioning
confidence: 99%
“…Social integration has the potential to foster and nurture resilience based competencies and may act as an important factor against the vicissitudes of life in old age [117]. Hayslip [118] a strong advocate for lifelong learning and the social integration of older people called for more intergenerational programs that engage young and older people in innovative and challenging learning enterprises. Machielse and Hortulanus [119] offered older people an important perspective on the need to establish a good working balance between independence and connectedness as "only then can they fully enjoy the freedom, and at the same time feel safe and protected in the face of limitations and adversity" (p. 135).…”
Section: Resilient Aging and Societal Responsibilitymentioning
confidence: 99%
“…Further support for this perspective comes from Hayslip (2014) who maintains that the antecedents, including the characteristics of successful lifelong learners must be understood for a lifelong learning approach to be successful and therefore proposes a focus on empowering individuals to be independent learners. This is supported by Claxton and Lucas's (2009) suggestion that dispositions, habits and beliefs underpin a positive and open-minded attitude to learning.…”
Section: What Is the Issue? Lifelong Learningmentioning
confidence: 99%